Technological factors affecting the performance of the restored concrete structures - Molodid, O.; Sharikina, N. (Ways to Improve Construction Efficiency, 2019)
The article presents the results of analytical studies of the scientific and technical literature in order to identify the technological factors that affect the physical and mechanical parameters of the restored concrete and reinforced concrete surface. The analysis revealed that during the restoration of concrete and reinforced concrete structures, physical and mechanical parts of the structure can be restored in case of change of technology of performance of works. Therefore, an important task is to identify the most influential technological factors that affect the performance of the restored reinforced concrete structures. These factors include: the state of the foundation of the restoration structure; method of applying repair materials; position of the repair surface relative to the horizon line; conditions of hardening of repair solution; sealing of repair material; in the arrangement of the contact layer, the dwell time between the application and its thickness; humidity of the restoring surface; ambient temperature during repair work. It is revealed that the method of application of the repair material, the humidity of the surface of the concrete structures, the thickness of the contact layer and the dwell time between the application to the concrete surface and the laying of the repair material, the method of surface treatment, and its condition affect the adhesion strength of the repair solution with the base, position in space and angle inclination to the horizon of the restoration structure influences the tensile strength in bending, water resistance, frost resistance and adhesion strength of the repair solution with the base, conditions and retention time of the formwork material in the formwork, affect the adhesion strength, water resistance, corrosion resistance and frost resistance of the restored area, compaction of the concrete mixture is an important technological factor that affects the compression and bending strength and uniformity of the repair material, and the duration of the repair of the seal. , the ambient temperature during the repair works is affecting the physical and mechanical performance of the restored concrete and reinforced concrete structures.